Hubungan Antara Pengetahuan Keluarga dan Dukungan Keluarga Dengan Kejadian Stroke Pada Lansia - Wulandari, Ria; Rimbawati, Yazika; Minata, Fika; Jaya KK, Indra Frana (JURNAL KESEHATAN TERAPAN, 2023)
Background: Stroke is a cerebrovascular disease (brain blood vessels) which is characterized byimpaired brain function due to damage or death of brain tissue due to reduced or blocked blood flowand oxygen to the brain. Objective: To determine the relationship between Family Knowledge andFamily Support with Stroke Incidence in the Elderly. This type of research uses an analytical surveymethod with a cross sectional approach. Sample in From the analysis results obtained that there is asignificant relationship between this study amounted to 36 people using accidental samplingtechnique. From the results of the analysis, it is known that there is a significant relationship betweenFamily Knowledge (ρ-value = 0.031), and family support (-value = 0.040), with the incidence ofstroke in the elderly in the Inpatient Room at Kayuagung Hospital, Ogan Komering Ilir Regency in2021. Suggestions : provide health education to families about stroke, treatment, rehabilitation, andcare for stroke patients at home. Nurses are also expected to help patients and families in increasingthe patient's motivation to recover.